RETRACTED: Voltammetry in the pharmaceutical analysis: A review - Aronbaev Sergey; Aronbaev Dmitry; Isakova Dilnosa (BIO Web of Conferences)
See the retraction notice BIO Web of Conferences 116, 00001 (2024), https://doi.org/10.1051/bioconf/202411600001